IMPLEMENTASI KEBIJAKAN TENTANG PELARANGAN MINUMAN BERALKOHOL (STUDI KASUS DI KECAMATAN KARANGAMPEL KABUPATEN INDRAMAYU) - Maftuhah .; Nurudin Siraj; Sri Wulandari (Jurnal Ilmiah Publika, 2017)
ABSTRACTThis thesis is the result of research conducted by researchers about: "IMPLEMENTATION POLICIES OF THE BAN ON ALCOHOL (CASE STUDY IN SUB Karangampel DISTRICT INDRAMAYU." Based on the study, researchers found some indicators of problem as much going on juvenile delinquency shown lately as fights individually or group, drunk-drunk, extortion, theft, thefts and assault in the District Karangampel Indramayu and juvenile delinquency is the case in the District Indramayu regency Karangampel today is perompokan and fights indicated by alcoholic beverages.The purpose of this study is to determine the implementation of policies on the prohibition of alcoholic beverages in an effort to tackle juvenile delinquency by Head in District Karangampel Indramayu district, to determine the factors of policy implementation prohibition of alcohol in the District Karangampel Indramayu district, to identify any obstacles faced by camat in the implementation of policies prohibiting alcoholic beverages in the district of Indramayu district Karangampel.This research uses descriptive method with qualitative approach, so that the data obtained through library and field study. In a literature study obtained data contained in books, websites etc. While field studies include observation, interviews, and documentation. This study uses the theory of Sabatier and Mazmanian which suggests three variables that affect the performance of the implementation which includes (1) the characteristics of the issues to be controlled; (2) the characteristics of the policy / legislation; (3) The policy environment variable. Furthermore, juvenile delinquency theories of juvenile delinquency Soetjiningsih that divides into (1) ordinary delinquency; (2) delinquency that leads to the violation; (3) Special delinquency.Based on the results of the study showed that the implementation of the policy of prohibition of alcoholic beverages in tackling juvenile delinquency in the district of Indramayu district Karangampel still not optimal. Because there are many sellers or merchants liquor clandestinely sell liquor to the public and are most often purchased to the merchant are teenagers.